HUBUNGAN PENGETAHUAN DAN SIKAP DENGAN PEMBERIAN ASI EKSKLUSIF DI POSYANDU ASOKA II KELURAHAN MANGASA KECAMATAN TAMALATE - Muhammad Fakhruddin (Jurnal Ilmiah Keperawatan dan Kebidanan Holistic Care, 2018)
ABSTRACT Objective: The purpose of this research is to know the relationship of knowledge and attitude with exclusive breast feeding at Posyandu Asoka II Kelurahan Mangasa District Tamalate 2015. Method: The research design used was observational analytic research with cross sectional approach. The population in this study were all mothers with infants aged 6-12 months. Results: The results of the study obtained from 30 respondents where mothers using exclusive breastfeeding with low knowledge of 10 people (33.3%) of respondents. While the mother is not using exclusive breastfeeding with low knowledge as much as 2 people (6.7%) of respondents. mothers using exclusive breastfeeding had high attitudes as many as 9 people (30.0%) of respondents and mothers using exclusive breastfeeding with low attitudes as many as 8 people (26.6%) respondents. While the mother is not exclusive ASI which has high attitude as much as 12 people (40,0%) responden and mother not using exclusive ASI which have low attitude as much as 1 person (3,3%) responder. Discussion: Exclusive breastfeeding is naturally produced by the mother who is destined for the baby is the right of the child. The government has also established that the baby be fed from birth until the age of 6 months but the reality in the field of society has not been able to implement it. Conclusion: From the data analysis using chi-square test that is p = 0,016 and p = 0,020 whose value is smaller than ? (0,05), it means Ho is rejected so that there is relationship between knowledge and attitude with exclusive breastfeeding at Posyandu Asoka II Kelurahan Mangasa Sub district Tamalate 2015. Suggestion: It is recommended to the government in order to improve the access of mother, family and community to information exclusive right breastfeeding and true